The Effect of Penetration, Availability, and Usage on Bank Profit - Rizky Wulan Suci; Brady Rikumahu (Almana : Jurnal Manajemen dan Bisnis, 2021)
National banking profit growth has been fairly good, seen from the results of the third quarter of 2017, large-scale banks that dominate the market have seen a significant increase. The increase in profit was due to the ability of banks to reduce costs and reduce the provision for bad loans. Financial inclusion, namely efforts to provide easy access, availability, and use of the formal financial system for all members of the economy without social exclusion. Financial inclusion has 3 indicators, namely penetration, availability, and usage. This study aims to determine the effect of penetration, availability, and usage on bank profits at 10 conventional commercial banks listed on the IDX. The independent variables are penetration, availability, and usage. The dependent variable is bank profit. This research uses quantitative methods and the purposive sampling technique. The author uses descriptive analysis and panel data regression analysis using fixed effects. The results showed that penetration, availability, and usage did not have a significant positive effect on bank profits. Banking companies should provide more effective financial services so that they benefit customers and attract investors.